THE RELATIONSHIP BETWEEN AGILITY AND DRIBBLING ABILITY OF BASKETBALL IN EXTRACURRICULAR STUDENTS OF SMAN 1 KEPAHIANG - Anggara, Deffri; Ritanza, Febra; Utama, Eko Putro; Ajayati, Titi; Destika, Vina; Jopin, Jopin (Perkumpulan Dosen Muda Bengkulu, 2024)
This study aims to determine the relationship between agility and basketball dribbling ability. The sample in this study were only male students totalling 20 people. This research method belongs to the type of quantitative research using correlational analysis techniques. Data collection techniques using the Illinois Agility Run Test agility test instrument and dribbling ability with a basketball dribbling ability test. The results of the study obtained tcount is greater than ttable or >, so it can be stated that the research hypothesis Ha is accepted and the hypothesis H0 is rejected. It can be seen from the calculation of the results that show the correlation value (r) with the provisions of the value of r = 0.657, the correlation coefficient is classified as strong. The results of the diterminan coefficient value show that the independent variable agility contributes to the dribbling ability of basketball by 44.16% and the remaining 55.84% is determined by other variables.